The role of the knowledge economy in human development in Sudan during the period from 1992 to 2022 - Ahmed, Mohamed Abdalla Mohamed (Journal of Economic, Administrative and Legal Sciences, 2025)
The paper aims to identify the roleof the knowledge economy in human development in Sudan during the period from 1992 - 2022, and the role of educational institutions in Sudan in transitioning to a knowledge economy, the paper assumed that the knowledge economy contributes to human development in Sudan, and that educational institutions in Sudan fulfill the requirements of building a knowledge society. The paper followed the deductive approach and the descriptive analytical approach to study the indicators of the knowledge economy, in addition to the comparative method to compare those indicators and then process them in order to reach Results: The paper reached conclusions, the most important of which is that the lack of the appropriate technical environment to stimulate the knowledge economy and material achievement in achieving human development in Sudan, and that the transition to knowledge economies still requires more effort at the level of all requirements in educational institutions. The paper recommended the necessity of linking education to the technology sector, keeping pace with the education outcomes of the knowledge based economy, and increasing financial allocations in the general budget for education and scientific research, especially in the field of cognitive technologies, and providing the necessary funding for scientific research so that these institutions can perform their role in producing knowledge and achieving human development in Sudan.